“Ruled By Fiction?” ‘Real’ Deception and Narrative Truth in Frank Rich’s The Greatest Story Ever Sold (2006) - Herrmann, Sebastian M. (Current Objectives of Postgraduate American Studies, 2012)
The Greatest Story Ever Sold: The Decline and Fall of Truth in Bush’s America“ is one representative of a series of highly popular, bestselling, creative non-fiction books that critique the Bush presidency. In his book, Frank Rich aims to unveil “the administration’s insidious efforts to blur the boundary between its“ reality and actual “reality“ (163, emphasis mine). This essay engages the book as a literary text and performs close readings to discuss the textual dynamics within Rich’s narrative project. More specifically, it will look at complexities and contradictions in the authentication strategies the text employs and at Rich’s attempts to tell a ‘true’ and credible narrative of the Bush administration’s deceit.